Microplastic Abundance in Mangrove Sediments Based on Mangrove Density at Cemara Beach, Jember - Debita Dwi Putri; Senki Desta Galuh; Winda Islamiyah Umarie; Latifa Mirzatika Al-Rosyid; Yuvita Dian Siswanti (ECOTON: Ecological Observation and Wetlands Conservation, 2026)
Mangrove ecosystems play an essential ecological role in coastal environments by stabilizing sediments and trapping various pollutants, including microplastics. Increasing plastic waste generated by human activities has contributed to the accumulation of microplastics in coastal ecosystems, particularly within mangrove sediments. This study aimed to analyze microplastic abundance in mangrove sediments based on mangrove density in the mangrove area of Cemara Beach, Puger, Jember. Sediment sampling was carried out at four observation points representing different environmental characteristics and levels of human activity, namely tourism areas, residential areas, central mangrove zones, and areas remote from human activities. Microplastic abundance was determined by calculating the number of particles identified in each sediment sample and expressing the results as particles per gram of sediment. The findings revealed that microplastics were present at all sampling locations with a total abundance of 0.885 particles/gram. The highest abundance was recorded at the residential area (0.650 particles/gram), while the lowest abundance was found at the site far from human activities (0.019 particles/gram). Mangrove density varied among observation points and contributed to sediment retention; however, microplastic abundance was not determined solely by vegetation density. Human activities, particularly those related to settlements and tourism, appeared to play a substantial role in increasing microplastic inputs into the mangrove ecosystem. These findings highlight the ecological function of mangroves as natural traps for microplastics and emphasize the need for improved coastal waste management and mangrove conservation to reduce microplastic contamination in coastal environments.